2014
DOI: 10.1590/s0100-83582014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of period of sugarcane cultivation on the abundance and distribution of weed seeds in the soil profile

Abstract: -An experiment was laid down in a screen house to determine the distribution of weed seeds at different soil depths and periods of cultivation of sugarcane in Ilorin, Nigeria. Soil samples from different depth levels (0-10 cm, 11-20 cm and 21-30 cm) were collected after harvesting of canes from three different land use fields (continuous sugarcane cultivation for > 20 years, continuous sugarcane cultivation for < 10 years after long fallow period and continuous sugarcane cultivation for < 5 years after long fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Concurrently, the presence of perennials (34.14%) indicates the suppressive impact on the annual weed variety within the fallow land. Previous studies in the same ecology reported 68% annuals and 32% perennials , 74% annuals and 26% perennials , 72% annuals and 28% perennials (Adereti et. al., 2014).…”
Section: Weed Species Compositionmentioning
confidence: 76%
“…Concurrently, the presence of perennials (34.14%) indicates the suppressive impact on the annual weed variety within the fallow land. Previous studies in the same ecology reported 68% annuals and 32% perennials , 74% annuals and 26% perennials , 72% annuals and 28% perennials (Adereti et. al., 2014).…”
Section: Weed Species Compositionmentioning
confidence: 76%